IoT-Based Water Quality Monitoring and Sustainable Modeling for Smart Campuses - Fachrul Kurniawan; Miladina Rizka Aziza; Novrindah Alvi Hasanah; Fadia Irsania Putri; Aji Prasetya Wibawa; Jehad Hammad; Yuhefizar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2026)
This study proposes an IoT-based water quality monitoring framework integrated with a continuous sustainable modeling approach for smart campus applications. A total of 404 sensor observations were collected, including pH, turbidity, temperature, and Total Dissolved Solids (TDS). A continuous water suitability score ranging from 0 to 1 was constructed based on WHO drinking water standards, and Multiple Linear Regression was employed to model the relationship between water quality parameters and the suitability score. The main contribution of this study lies in the development of a lightweight analytical framework that combines continuous regression modeling with threshold-based classification to support real-time decision-making in resource-constrained environments. The dataset was divided into 90% training and 10% testing data. The results show that the proposed framework achieved a classification accuracy of 88.5% based on threshold mapping of regression outputs, with a misclassification rate of 11.5%. These findings demonstrate the effectiveness of integrating IoT-based monitoring with interpretable and computationally efficient analytical models for sustainable campus water management.